2020
DOI: 10.21037/tcr.2020.04.12
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression integrated analysis and identification of novel biomarkers in small cell lung cancer: a meta-analysis

Abstract: Background Small cell lung cancer (SCLC) is an aggressive and recalcitrant cancer. In recent years, studies focused on the abnormal expression of microRNA which has proven valuable in terms of prognosis, diagnosis and treatment in SCLC. To address the limitations of independent studies data, a meta-analysis seems necessary for further exploration of microRNA as biological target and regulatory factor in SCLC. Methods We performed comprehensive literature retrieval in GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Our findings showed that hsa-miR-200b-3p was overexpressed in MPE, suggesting that it has the potential to serve as a biomarker to distinguish between benign and malignant PE. It was reported that hsa-miR-182-5p was upregulated in small cell lung cancer (34), ovarian cancer (35), and LUAD (36). Moreover, hsa-miR-629-5p was highly expressed in bladder urothelial carcinoma (37).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that hsa-miR-200b-3p was overexpressed in MPE, suggesting that it has the potential to serve as a biomarker to distinguish between benign and malignant PE. It was reported that hsa-miR-182-5p was upregulated in small cell lung cancer (34), ovarian cancer (35), and LUAD (36). Moreover, hsa-miR-629-5p was highly expressed in bladder urothelial carcinoma (37).…”
Section: Discussionmentioning
confidence: 99%
“…It also included miR-451a-5p, an erythroid cell-specic miR that has been linked to erythroid maturation and has shown potential as a biomarker for cancer diagnosis, prognosis, and treatment in several studies. 73,74 Finally, miR-193a-5p was included, a miR that has been shown to be dysregulated in tumor cells and has a dual role in carcinogenesis, being up-regulated in prostate cancer but down-regulated in colorectal cancer. [75][76][77] Additionally, recent studies have reported that miR-193a-5p levels increase in the serum of patients with liver injury.…”
Section: Testing Mir-122-5p In Single-plexmentioning
confidence: 99%
“…MicroRNAs (miRs) are small non-coding RNA molecules that have emerged as promising candidates as circulating biomarkers. [9][10][11][12][13] They play critical roles in various physiological and pathological processes, including DILI. [14][15][16][17] Among the miRs implicated in DILI, miR-122-5p has garnered significant attention.…”
Section: Introductionmentioning
confidence: 99%